Point of care high resolution ultrasound in the evaluation of Bangladeshi women presenting to a breast care center (Bangladesh Medical Journal Khulna, 2017)
Background: Mammography and ultrasound examinations for diagnosis and staging of breast problems have been traditionally performed in specialized facilities, which circumstances are associated with increased costs and inconvenience for patients. Point of care or clinical office provision of high resolution ultrasound may allow addressing these equity barriers to health services, but there are limited data in Bangladesh about such practice and the associated quality of care.Objective: To ascertain the advantage of ultrasonogram in the diagnosis of breast disease and screening of breast cancer.Methods: From February through November 2014, 1085 women presented to the Amader Gram Breast Care Center in Khulna. In each of these women in addition to standard history and physical examination, a high resolution ultrasound scan was performed of both breasts. Standard clinical and ultrasound practice definitions of breast conditions were applied to each case by an specialist surgeon trained in breast sonology.Results: Two thirds of women had history, physical examination and ultrasound findings consistent with fibrocystic conditions. 12% had fibro adenomas, 5% inflammatory infectious conditions, 2% obvious or strongly suspected breast malignacy, and 1% had masses of uncertain nature. 3% had more than one abnormal breast condition and 3% had no breast abnormalities at all. The overwhelming majority of women benefitted from having ultrasound examination which contributed to prompt, definitive characterization of their breast conditions and which pictorial demonstration contributed to patient education about the clinical diagnosis.Conclusion: Point of care high resolution breast ultrasound can contribute favorably to quality and equity of care for Bangladeshi women with breast problems.Bang Med J (Khulna) 2016; 49 : 3-6